2008
DOI: 10.1007/s11999-008-0604-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Results Between Lateralized Single- and Double-bundle ACL Reconstructions

Abstract: Level II, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 56 publications
2
64
0
Order By: Relevance
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] However, at least 2 randomized clinical studies have reported a lower risk of graft failure with double-bundle ACL reconstruction. [6][7][8] Many important factors, such as the timing of the operation, fixation methods, and other details in the surgical technique, vary in all of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] However, at least 2 randomized clinical studies have reported a lower risk of graft failure with double-bundle ACL reconstruction. [6][7][8] Many important factors, such as the timing of the operation, fixation methods, and other details in the surgical technique, vary in all of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…§ Several biomechanical and clinical DB-ACLR studies also report fixing the AM and PL bundle grafts at the same knee flexion angle simultaneously, usually between 0°and 30°of knee flexion. 3,19,22,24,25,28,34,36,43 Previous biomechanical studies have demonstrated that graft fixation angles affect knee kinematics after a DB-ACLR. 9,26,38 It was reported that fixation of the AM graft at 60°and the PL graft at 0°overloaded the AM graft, while fixing both the AM and PL grafts at 30°overloaded the PL graft compared with the intact bundles.…”
mentioning
confidence: 99%
“…ACL reconstruction is favored for younger and more active patients, allowing for an earlier return to activities and competitive sport (3). Some studies have reported comparable outcomes for double-bundle and single-bundle ACL reconstruction, with no differences in clinical knee scores and knee extension and flexion muscular strength between the two graft types (4,5). Hamstring autograft is primarily used for double-bundle ACL recon-struction.…”
Section: Introductionmentioning
confidence: 99%